2002
DOI: 10.1034/j.1399-302x.2002.170409.x
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of viridans group streptococci to sialic acid‐, galactose‐ and N‐acetylgalactosamine‐containing receptors

Abstract: The binding of 10 viridans group streptococci to sialic acid-, galactose (Gal)- and N-acetylgalactosamine (GalNAc)-containing receptors was defined by analysis of the interactions between these bacteria and structurally defined glycoconjugates, host cells and other streptococci. All interactions with sialic acid-containing receptors were Ca(2+)-independent as they were not affected by ethyleneglycoltetraacetic acid (EGTA), whereas all interactions with Gal- and GalNAc-containing receptors were Ca(2+)-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
41
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 34 publications
4
41
0
Order By: Relevance
“…35 Coaggregation of Streptococcus viridans, a member of the oral flora, was inhibited by the addition of oligosaccharides containing Gal and/or GalNAc, 36 strongly suggesting that Gal/GalNAc residues were exposed on the surfaces of Streptococci. Another study showed that Gal and GalNAc residues were present in an exo-polysaccharide or a capsular polysaccharide produced by Lactobacillus.…”
Section: Discussionmentioning
confidence: 99%
“…35 Coaggregation of Streptococcus viridans, a member of the oral flora, was inhibited by the addition of oligosaccharides containing Gal and/or GalNAc, 36 strongly suggesting that Gal/GalNAc residues were exposed on the surfaces of Streptococci. Another study showed that Gal and GalNAc residues were present in an exo-polysaccharide or a capsular polysaccharide produced by Lactobacillus.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial strains and growth conditions: The S. gordonii strains used in this study included DL1 (Challis strain, wild type, biovar 2) (12,22) and its hsa mutant EM230 (DL1 hsa::ermAM) (8) as well as several other wild-type S. gordonii strains, including 38, SK6 (biovar 1), M5, 10558 (biovar 2), and SK12 (biovar 3) (12,22). All streptococci were cultured overnight in brain-heart infusion broth (Difco, Becton-Dickinson and Company, Sparks, MD, USA) at 37 C. The medium was supplemented with 10 µg mL of erythromycin (Sigma-Aldrich, St. Louis, MO, USA) as needed.…”
Section: Methodsmentioning
confidence: 99%
“…Host sialic acid-containing receptors for Hsa adhesin include the salivary mucin MG2 (11,12), leukosialin (CD43) (13), platelet glycoprotein Ibα (14), erythrocyte glycophorin A and band3 (15), and leukocyte CD11b and CD50 (16). The Hsa adhesin and its homologs facilitate attachment of S. gordonii to host cells, such as polymorphonuclear leukocytes (13,16), erythrocytes (7,15), platelets (9,14,17,18), macrophages, and monocytes (19).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously identified and functionally characterized the gene (hsa) encoding the sialic acidbinding adhesin (Hsa) of S. gordonii DL1, a glycoprotein containing GlcNAc (24,25,27). Hsa binds α2-3-linked sialic acid termini of O-glycosylated mucin-type glycoproteins, including salivary mucin MG2 and leukosialin, the major surface glycoprotein of human polymorphonuclear leukocytes (20,21,(24)(25)(26).…”
mentioning
confidence: 99%
“…We have previously identified and functionally characterized the gene (hsa) encoding the sialic acidbinding adhesin (Hsa) of S. gordonii DL1, a glycoprotein containing GlcNAc (24,25,27). Hsa binds α2-3-linked sialic acid termini of O-glycosylated mucin-type glycoproteins, including salivary mucin MG2 and leukosialin, the major surface glycoprotein of human polymorphonuclear leukocytes (20,21,(24)(25)(26).We have also shown that the aggregation of human platelets by S. gordonii DL1, an interaction implicated in the pathogenesis of infective endocarditis (11), required the expression of hsa (27). In addition, neuraminidase-treatment of the platelets abolished this interaction, further supporting the essential role of Hsa in the bacteria-platelet interaction (27).…”
mentioning
confidence: 99%